Effects of Hexavalent Chromium (Cr+6) on Gold Fish (Carassius auratus L.) - Hanan J. Ashur; Hussain A. M. Dauod; Mahdi T. Muhaisen (Journal of Madenat Alelem University College, 2011)
Groups of gold fish (Carassius auratus) treated with different concentrations of hexavalent chromium (Cr+6), to study the acute toxic effects and determine the (Lc50). The results of the study revealed that (Lc50) was 72.5 mg/L during the period of (96 hrs). On the other hand the study designed to investigate the chronic effects of three different sublethal concentrations of hexavalent chromium on fish under investigation. Results showed some behavioral changes represented by rapid and erratic swimming, rapid respiration, weak responses to outer stimulus, convulsions, lethargy and low appetite. The results also showed some changes in growth represented by significance decrease in mean body weight. Histopathological changes of kidney were represented by narrowing of tubules lumen, hyperplasia, blood congestion hemorrhage and fibrosis of the glomerulus. These were increased with the increasing of the concentration. The results of bioaccumulation study revealed an increased in accumulation of chromium in the flesh (muscles) of fish with the increasing of the concentration and the mean values were 3.5, 8.62 and 9.0 mg/L in concentrations of 10, 20 and 30 respectively.